2022
DOI: 10.3389/fchem.2022.1008568
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-free approach to quinolines via direct oxidative cyclocondensation reaction of N,N-dimethyl enaminones with o-aminobenzyl alcohols

Abstract: A transition-metal-free method for the construction of 3-substituted or 3,4-disubstituted quinolines from readily available N,N-dimethyl enaminones and o-aminobenzyl alcohols is reported. The direct oxidative cyclocondensation reaction tolerates broad functional groups, allowing the efficient synthesis of various quinolines in moderate to excellent yields. The reaction involves a C (sp3)-O bond cleavage and a C=N bind and a C=C bond formation during the oxidative cyclization process, and the mechanism was prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Intermediates, 3a–c , were synthesised via condensation reaction of aniline derivatives 1a–c and dimedone 2 in acidic media using dichloromethane (DCM) as a solvent 42 ( Scheme 1 ). These intermediates, 3a–c , were reacted with ethyl cyanoacetate 4 and appropriate aryl aldehydes; o -substituted benzaldehydes 5a–c , p -substituted benzaldehydes 7a–e , disubstituted benzaldehydes 9a,b , or pyridine carboxaldehydes ( ortho or meta ) 11a,b , in absolute ethanol as a solvent and piperidine as a catalyst via cyclocondensation mechanism 43 , 44 to yield targeted compounds, 6a–i , 8a–m , 10a–d , and 12a–f as a racemic mixture ( Scheme 2 ). This reaction was accomplished in two steps; the first step was Knoevenagel condensation between aryl aldehyde and ethyl cyanoacetate leading to the formation of unsaturated nitrile 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Intermediates, 3a–c , were synthesised via condensation reaction of aniline derivatives 1a–c and dimedone 2 in acidic media using dichloromethane (DCM) as a solvent 42 ( Scheme 1 ). These intermediates, 3a–c , were reacted with ethyl cyanoacetate 4 and appropriate aryl aldehydes; o -substituted benzaldehydes 5a–c , p -substituted benzaldehydes 7a–e , disubstituted benzaldehydes 9a,b , or pyridine carboxaldehydes ( ortho or meta ) 11a,b , in absolute ethanol as a solvent and piperidine as a catalyst via cyclocondensation mechanism 43 , 44 to yield targeted compounds, 6a–i , 8a–m , 10a–d , and 12a–f as a racemic mixture ( Scheme 2 ). This reaction was accomplished in two steps; the first step was Knoevenagel condensation between aryl aldehyde and ethyl cyanoacetate leading to the formation of unsaturated nitrile 45 .…”
Section: Resultsmentioning
confidence: 99%
“…25 Subsequently, Yu et al demonstrated the synthesis of 3-aroylquinolines via the direct oxidative cyclocondensation of N , N ′-dimethyl enaminones with 2-aminobenzyl alcohols in the presence of potassium persulfate. 26 John et al described a [4+2] Diels Alder cycloaddition route toward 3-aroyl quinolines from enaminones and generated aza- o -quinone methides from 2-aminobenzyl chloride in situ . 27 In a complementary route, it was shown that the reaction between enaminone and benzisoxazole in the presence of a ruthenium catalyst under an acidic medium afforded 3-aroyl quinolines.…”
Section: Introductionmentioning
confidence: 99%
“…in the silylation of C−H bonds in aromatic heterocyclic compounds. Subsequently, Yu and co‐workers reported the t BuOK‐mediated acceptorless dehydrogenation of N‐heterocyclic compounds [26,27] …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Yu and co- workers reported the t BuOK-mediated acceptorless dehydrogenation of N-heterocyclic compounds. [26,27] Transition metal-free and base catalyst-mediated construction of TSCs from alcohols is still not explored. In contemplating this, we have investigated a metal-free methodology to synthesize highly important TSCs utilizing base catalysts through the dehydrogenative coupling of alcohols and substituted thiosemicarbazides.…”
Section: Introductionmentioning
confidence: 99%